Can positive welfare counterbalance negative and can net welfare be assessed? - Broom, Donald M. (Frontiers in Animal Science, 2023)
The absence of poor welfare is important for welfare to be good, but measures of good welfare are of great value in welfare assessment. Assessors of the welfare of individuals need to know the overall balance of good and poor. Direct behavioural measures and measures of physiology, such as oxytocin concentration, together with experimental studies of motivation, help in evaluating whether positive or negative components of welfare are prevailing in a given situation. Studies of humans and other animal species are described. While there are few detailed comprehensive studies measuring positive and negative welfare in the same individuals, examples are given of overall measurements of consequences when there could be positive and negative effects. Measures of net welfare, when positive and negative components have been resolved, are described. It is concluded that good welfare can often counterbalance poor welfare but does not do so in all circumstances.